No Place like Utopia / Photographs - Maryana Kovalchuk, (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
Living in today’s world, where truth is only attainable in plural form, would it be possible to free our environment from ideological forms and superstructures? Utopian thinking might not be the key to ending this problem rather than revealing its true nature.